The Magellania venosa Biomineralizing Proteome: A Window into Brachiopod Shell Evolution - Jackson, Daniel J. (Genome Biol Evol, 2015)
Brachiopods are a lineage of invertebrates well known for the breadth and depth of their fossil record. Although the quality of this fossil record attracts the attention of paleontologists, geochemists, and paleoclimatologists, modern day brachiopods are also of interest to evolutionary biologists due to their potential to address a variety of questions ranging from developmental biology to biomineralization. The brachiopod shell is a composite material primarily composed of either calcite or calcium phosphate in close association with proteins and polysaccharides which give these composite structures their material properties. The information content of these biomolecules, sequestered within the shell during its construction, has the potential to inform hypotheses focused on describing how brachiopod shell formation evolved. Here, using high throughput proteomic approaches and next generation sequencing, we have surveyed and characterized the first shell-proteome and shell-forming transcriptome of any brachiopod, the South American Magellania venosa (Rhynchonelliformea: Terebratulida). We find that the seven most abundant proteins present in the shell are unique to M. venosa, but that these proteins display biochemical features found in other metazoan biomineralization proteins. We can also detect some M. venosa proteins that display significant sequence similarity to other metazoan biomineralization proteins, suggesting that some elements of the brachiopod shell-forming proteome are deeply evolutionarily conserved. We also employed a variety of preparation methods to isolate shell proteins and find that in comparison to the shells of other spiralian invertebrates (such as mollusks) the shell ultrastructure of M. venosa may explain the effects these preparation strategies have on our results.